How does the implementation of counter terrorism measures impact on human rights in Kenya and Uganda? - Nyaundi, Kennedy Monchere (2014)
Includes bibliographical references.This thesis explores the impact of counter terrorism measures on human rights in Kenya and Uganda. It identifies terrorism as a global problem and reviews its common features. It recognises that the human cost of terrorism has been felt in virtually every corner of the world. It analyses the nature and scope of trends of terrorist activities in Kenya and Uganda, offers possible reasons for the increase of incidents of terror and considers the challenges in combating terrorism in these countries. The thesis outlines the fundamental freedoms that are most commonly engaged in the fight against terrorism and describes states’ obligations in respect of those rights. It recognises that a significant effect of terrorist activity is the tendency to pit security against human rights. It demonstrates that legislation intended to strengthen anti terrorism efforts raise serious concerns in relation to international and domestic human rights law. The thesis investigated one central concern: How does the implementation of counter terrorism measures impact on human rights in Kenya and Uganda? To answer this question, the study sought to investigate several related questions: In the enforcement of counter terrorism measures, is it possible for governments to play by the constraints of the rule of law? Is freedom during times of emergency as important as during peacetime? Is it possible and practical to observe art 4 of the ICCPR in the war against terrorism or should a lower threshold be established